В ім'я милої вітчизни: вірність та зрада Івана Мазепи - Плохій, С. (Соціум. Альманах соціальної історії, 2006)
The author studies the transformation of the concept of «motherland» in the community of the Cossacks elite of the second half of the 17th - early 18th century: starting from the traditional for the Polish-Lithuanian Commonwealth view on motherland as «Old Ruthenia» up to identifying it as the Hetmanate. Therefore
the author claims that the concept of «motherland» was basic for the attempts both to legitimize and to discredit Mazepa's uprising against the tsar in 1708.

Mazepa and his supporters explained their uprising by their agitation for motherland's integrity and welfare, as the attempt to liberate it from foreign yoke. There were Mazepa's speeches and manifests that had introduces the concept of motherland as highest value and the object of fidelity. Due to this rhetoric, Peter I, speaking primarily about Mazepa's treason of the tsar himself, later turned to speak about his treason of motherland. On the contrary, the tsar trayed to present his actions as the defense of «Little Russians nation» against it's enemies, that were moved by personal ambitions and the intention to enrich theirselve. It is important, that, addressing to his «Little Russian» subjects, Peter I speaks about «their» (not «our») motherland; on the contrary pronoun «our» is widely used by the representatives of the Church and civil elites of the Hetmanate.

The author also describes the appearance of the concept of Russian monarchy (thanks to Theophan Prokopovych) as common motherland and object of fidelity of all the subjects of the tsar, and analyses its controversial representation in Hrabianka and Velychko discourses. Finally, the author notes, that in the drama «Grace of God», presented by students of the Kyiv-Mohyla Academy to honor the restoration of the Hetmanate, the concept of motherland equals Ukraine, or Little Russia, not Russia. This demonstrates that the tradition of Mazepa and Orlyk dominated in the Hetmanate over the tradition of Prokopovych.